The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00011-015-0828-7
|View full text |Cite
|
Sign up to set email alerts
|

TLR1 expression in mouse brain was increased in a KA-induced seizure model

Abstract: These results demonstrate that cortical and hippocampal sub-regional expression of TLR1 is altered during epileptogenesis in a time- and location-specific manner, suggesting a close association with the process of epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In agreement with previous studies, KA injection (15 mg/kg, i.p.) induced epileptic seizures in this study [ 36 , 41 43 ]. SAHA pretreatment (10 or 50 mg/kg) reduced KA-induced neuronal apoptosis, suggesting SAHA as a potent neuroprotective and anticonvulsant agent.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies, KA injection (15 mg/kg, i.p.) induced epileptic seizures in this study [ 36 , 41 43 ]. SAHA pretreatment (10 or 50 mg/kg) reduced KA-induced neuronal apoptosis, suggesting SAHA as a potent neuroprotective and anticonvulsant agent.…”
Section: Discussionmentioning
confidence: 99%
“…Different stimuli may lead to increased expression of microglia TLRs, such as hypoxia (Smith et al, 2013 ; Yao et al, 2013 ), LPS (Kielian et al, 2005 ; Yousif et al, 2018 ), Poly(I:C; Yousif et al, 2018 ), kainic acid (Wang et al, 2015 ; Hu and Mao, 2016 ), α-synuclein (Béraud et al, 2011 ; Daniele et al, 2015 ) and amyloid beta (Aβ; Jana et al, 2008 ; Richard et al, 2008 ; Caldeira et al, 2017 ).…”
Section: Tlr Expression In the Cnsmentioning
confidence: 99%
“…Following injury, activation of these toll-like receptors can contribute to continued glutamate excitotoxicity out to several weeks [59]. Wang and colleagues showed that toll-like receptors are upregulated following kainic acid administration [60]. Specifically, toll-like receptor 4 is associated with temporal lobe seizures following trauma [61].…”
Section: Neuroinflammationmentioning
confidence: 99%